Agrarian Crisis In India - Reddy, D Narasimha; Mishra,Srijit (New Delhi Oxford University, 2009)
This book presents the all-pervasive crisis in India's agrarian economy that has been marked with deceleration in growth and farmer distress for more than a decade. The most stark feature of this volume-case studies on farmer suicides-throws open the underlying causes of the deep rooted sluggish state of agriculture.
Keywords: Agricultural Economics; Agriculture-India